Use of ecstasy and other psychoactive substances among school-attending adolescents in Taiwan: national surveys 2004-2006 - Huang Wei-Lun; Ting Te-Tien; Fu Tsung-Chieh; Chen Wei J; Tang Guang-Mang; Hsiao Chuhsing; Chen Chuan-Yu (BMC, 2009)
Abstract Background With the backdrop of a global ecstasy epidemic, this study sought to examine the trend, correlates, and onset sequence of ecstasy use among adolescents in Taiwan, where a well-established gateway drug such as marijuana is much less popular. Methods A multistage probability survey of school-attending adolescents in grades 7, 9, 10, and 12, aged 11-19 years, was conducted in 2004, 2005, and 2006. A self-administered anonymous questionnaire elicited response rates ranging from 94.3% to 96.6%. The sample sizes were 18232 respondents in 2004, 17986 in 2005, and 17864 in 2006. Results In terms of lifetime prevalence and incidence, ecstasy and ketamine by and large appeared as the first and second commonly used illegal drugs, respectively, among middle (grades 7 and 9) and high school students (grades 10 and 12) during the 3-year survey period; however, this order was reversed in the middle school-aged students starting in 2006. Having sexual experience, tobacco use, and betel nut use were factors consistently associated with the onset of ecstasy use across years. The majority of ecstasy users had been involved in polydrug use, such as the use of ketamine (41.4%-53.5%), marijuana (12.7%-18.7%), and methamphetamine (4.2%-9.5%). Conclusion From 2004 to 2006, a decline was noted in the prevalence and incidence rate of ecstasy, a leading illegal drug used by school-attending adolescents in Taiwan since the early 2000s. The emerging ketamine use trend may warrant more attention in the future.